Analisis Pengaruh Sosial Ekonomi Terhadap Tingkat Pengangguran Terbuka (Studi Kasus 6 Provinsi Termiskin Di Indonesia) - Mangopa, Jesika Yuliani; Canon, Syarwani; Saleh, Sri Endang; Arham, Muhammad Amir; Bumulo, Frahmawati (Economics and Digital Business Review, 2023)
This research aimed to analyze the extent of the influence of the Regional Minimum Wages, Population Growth, and Human Development Index (HDI) on the Open Unemployment Rate in the 6 Poorest Provinsi in Indonesia. The data used in this research were secondary data obtained from Statistics Indonesia (BPS) during the 2013-2022 period, and the unit of analysis was six provinces classified as the poorest in Indonesia. This research employed multiple linear regression analysis panel data analysis with the Random Effect Model (REM) method. The research findings indicated that (1) Regional Minimum Wage influenced the reduction of Open Unemployment Rate negatively and significantly, meaning that every increase in the Wage could reduce unemployment in six Indonesian poorest provinsi, (2) Population Growth influenced the increase in Open Unemployment Rate positively and significantly, meaning that every 1% increase in the population growth could increase unemployment in six Indonesian poorest provinces, and (3) The Human Development Index influenced the increase in Open Unemployment Rate positively and significantly, meaning that every 1% increase in the HDI could increase unemployment in six Indonesian poorest provinces.